Law Enforcement Against Notary for Loss Olographic Will - Imanuel Santoso, Debora; Maskanah, Ummi; Narsudin, Udin (International Journal of Latin Notary, 2024)
The notary has the duties and responsibilities of making and at the same time keeping the olographic inheritance deed desired by the heir before he dies, which is written manually and contains the distribution of his inheritance after he dies without the potential heirs knowing. However, there are times when the olographic will is lost or damaged due to the notary's negligence, resulting in a loss to the maker of the olographic will. This study uses a descriptive normative juridical method; secondary data will be analyzed qualitatively through primary and secondary legal materials supplemented by interviews with notaries using purposive sampling. From the results of the research, it is known that based on Article 933 of the Civil Code requires that the will be submitted to a notary to be stored and sent to the Probate Court and the Central List of Wills. Furthermore, Article 1 paragraph (13) states that the notary has the duty and responsibility to keep the olographic will. Therefore, if the olographic kept by the notary is lost and or damaged, in addition to violating the code of ethics, it also violates Article 1365 of the Criminal Code in conjunction with Article 1367 of the Criminal Code so that the notary can be held accountable by the injured party based on Article 84 UUJN. 7 of 2016.